Characterisation of Haemolytic Uropathogenic Escherichia coli Isolated From Dogs and Cats - Sarah Büttner; Joachim Spergser; Olga Makarova; Michael P. Szostak; Adriana Cabal Rosel; Werner Ruppitsch; Sabine Schäfer‐Somi; Elke Müller; Sascha D. Braun; Stefan Monecke; Ralf Ehricht; Frank Künzel; et al. (Veterinary Medicine and Science, 2026)
ABSTRACT Background Escherichia ( E .) coli is the primary cause of urinary tract infections in companion animals. Objectives Therefore, the present study aimed to characterise antimicrobial resistance profiles, virulence‐associated genes, and phylogenetic diversity of E. coli with haemolytic colony morphology isolated from urine samples of cats and dogs during routine diagnostic activities, which have not been characterised previously in Austria. Methods A total of 51 isolates were included from dogs ( n = 32) and cats ( n = 19) and characterised by a polyphasic approach, including susceptibility testing and DNA microarray‐based assays. In addition, all isolates were analysed using two‐locus fumC and fimH sequence typing (CH‐clonotyping) and E. coli phylotyping. Results The majority of E. coli isolates belonged to phylogenetic group B2, with one isolate assigned to phylogenetic group B1. Thirty‐four CH‐clonotypes were detected using two‐locus sequence typing. All isolates detected could be classified as ExPEC. Conclusions The identification of clonal complexes common to humans indicates interspecies transmission, thereby emphasising the critical need for surveillance in companion animal populations.